Abnormal respiration under hyperoxia in TASK-1/3 potassium channel double knockout mice - Bühler, Philipp K.; Heitzmann, Dirk (Respiratory physiology & neurobiology, 2017)
Despite intensive research, the exact function of TASK potassium channels in central and peripheral chemoreception is still under debate. In this study, we investigated the respiration of unrestrained TASK-3 (TASK-3−/−) and TASK-1/TASK-3 double knockout (TASK-1/3−/−) adult male mice in vivo using a plethysmographic device. Ventilation parameters of TASK-3−/− mice were normal under control condition (21% O2) and upon hypoxia and hypercapnia they displayed the physiological increase of ventilation. TASK-1/3−/− mice showed increased ventilation under control conditions. This increase of ventilation was caused by increased tidal volumes (VT), a phenomenon similarly observed in TASK-1−/− mice. Under acute hypoxia, TASK-1/3−/− mice displayed the physiological increase of the minute volume. Interestingly, this increase was not related to an increase of the respiratory frequency (fR), as observed in wild-type mice, but was caused by a strong increase of VT. This particular respiratory phenotype is reminiscent of the respiratory phenotype of carotid body-denervated rodents in the compensated state. Acute hypercapnia (5% CO2) stimulated ventilation in TASK-1/3−/− and wild-type mice to a similar extent; however, at higher CO2 concentrations (>5% CO2) the stimulation of ventilation was more pronounced in TASK-1/3−/− mice. At hyperoxia (100% O2), TASK-1−/−, TASK-3−/− and wild-type mice showed the physiological small decrease of ventilation. In sharp contrast, TASK-1/3−/− mice exhibited an abnormal increase of ventilation under hyperoxia. In summary, these measurements showed a grossly normal respiration of TASK-3−/− mice and a respiratory phenotype of TASK-1/3−/− mice that was characterized by a markedly enhanced tidal volume, similar to the one observed in TASK-1−/− mice. The abnormal hyperoxia response, exclusively found in TASK-1/3−/− double mutant mice, indicates that both TASK-1 and TASK-3 are essential for the hyperoxia-induced hypoventilation. The peculiar respiratory phenotype of TASK-1/3 knockout mice is reminiscent of the respiration of animals with long-term carotid body dysfunction. Taken together, TASK-1 and TASK-3 appear to serve specific and distinct roles in the complex processes underlying chemoreception and respiratory control.
Gesehen am 21.08.2018